PERENCANAAN JARINGAN NIRKABEL BROADBAND WIRELESS ACCESS (BWA) 802.16a/e WiMAX FREKUENSI 3.3 GHz UNTUK APLIKASI NEIGHTBOUR COMMUNITY PADA PERUMAHAN GRAND DEPOK CITY DEPOK - Yahdi Kusnadi (LPPM Universitas Bina Sarana Informatika, 2010)
One application of the use of Broadband Wireless Access (BWA) is established between the ease of personnel in a large environment. Current technology used for the VSAT (Very Small Aperture Terminal), which uses satellites. However, the technology is quite expensive operating costs so that the use of this technology requires a high cost. Therefore, alternative technologies are relatively inexpensive and reliable is the Broadband Wireless Access (BWA) using 802.11b / g WiFi or 802.16a/e WiMAX.Keywords: Broadband Wireless Access, QoS management, 802.11b / g WiFi, 802.16a / e WiMAX.